Overview of Hemoglobin Levels in Pregnant Women in the Working Area of Delitua Community Health Center in 2024 - Grace Hanshella; Sinurat, Samfriati; Siallagan, Ance (Jurnal Kesehatan dan Kedokteran, 2026)
Anemia during pregnancy remains a significant maternal health problem because it can increase the risk of complications for both mother and fetus. Operationally, anemia in pregnancy is defined as hemoglobin (Hb) levels below 11 g% in the first and third trimesters and below 10.5 g% in the second trimester. Local data are needed to describe the magnitude of the problem and to support strengthening screening and education services at primary healthcare facilities. Objective: This study aimed to determine the profile of hemoglobin levels among pregnant women in the working area of the Delitua Community Health Center in 2024. Methods: This study employed a descriptive quantitative design. The population consisted of 245 pregnant women based on Delitua Community Health Center data as of July 2024. A total of 31 respondents were selected using non-probability sampling, specifically convenience sampling. Data were collected using observation sheets and hemoglobin measurements with the EasyTouch GCHb device, and analyzed descriptively using frequency and percentage distributions. Results: Most respondents were in the late adulthood age group (48.4%), the majority were in the third trimester (77.4%), and most were multigravida (77.4%). The distribution of hemoglobin levels showed that 64.5% of pregnant women were classified as anemic. Implications: These findings highlight the need to strengthen routine Hb screening during pregnancy, improve adherence to iron (Fe) tablet consumption, enhance nutritional intake, and intensify structured education and counseling through Posyandu and antenatal care services to reduce anemia prevalence among pregnant women. Originality/Value: This study provides a localized profile of hemoglobin levels among pregnant women in the Delitua primary healthcare setting in 2024, offering context-specific evidence to support program planning, risk mapping, and evaluation of anemia prevention interventions at the primary care level.